Gyrosigma rostratum sp. nov. (Bacillariophyta) from the low intertidal zone, Xiamen Bay, southern China - Liu, Bing; Williams, David M.; Huang, Bangqin (Phytotaxa, 2015)
Gyrosigma rostratum, sp. nov., a new diatom species from the low intertidal zone, Xiamen Bay, southern China, was studied with light and scanning electron microscopy. The valves are lanceolate with protracted rostrate apices, symmetrical to both apical and transapical axis, not sigmoid. The raphe is straight, with a raphe angle of approximately two degrees. The external central raphe endings turn in the same direction and are isomorphic. The unique characteristic of the valve is that a conopeum (a lunate flap of silica, approximately 0.8–1.1 µm wide by 4.4–4.8 µm long) covers the terminal axial area and two rows of areolae near each apex. Gyrosigma rostratum is epipsammic and lives in marine habitats.